2016
DOI: 10.1111/1467-9604.12139
|View full text |Cite
|
Sign up to set email alerts
|

Management of inclusive education in Oman: A framework for Action

Abstract: Inclusive education (IE) and the special education services related to it are relatively new in Oman. Efforts to manage special/inclusive education face many challenges due to a number of culturally rooted factors. Further, empirical research on IE in Oman is scarce and there is a need to advance IE discourse based on empirically validated perspectives. This article examines how IE is managed in schools from the perspective of school leaders in order to develop a framework for action. The author conducted a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Parents' positive attitudes and efforts for inclusion have helped integrate children with disabilities into mainstream education (Sharma & Trory, 2019). In his qualitative inquiry in the Omani context, Emam (2016) asserted that efforts to manage IE face many challenges due to a number of culturally rooted factors. Similarly, in their study on prospective early childhood teachers' attitudes towards IE, Fayez et al (2011) revealed that deeply rooted barriers within the macro societal and cultural contexts would encumber successful inclusion in Jordan.…”
Section: At T I T U De S Towa R D S I Ementioning
confidence: 99%
See 1 more Smart Citation
“…Parents' positive attitudes and efforts for inclusion have helped integrate children with disabilities into mainstream education (Sharma & Trory, 2019). In his qualitative inquiry in the Omani context, Emam (2016) asserted that efforts to manage IE face many challenges due to a number of culturally rooted factors. Similarly, in their study on prospective early childhood teachers' attitudes towards IE, Fayez et al (2011) revealed that deeply rooted barriers within the macro societal and cultural contexts would encumber successful inclusion in Jordan.…”
Section: At T I T U De S Towa R D S I Ementioning
confidence: 99%
“…In Egypt, the rationale for IE emanated from a rights‐based approach, influenced by significant international declarations concerning IE, which is conceived as a constructive approach for integrating pupils who have disabilities in to the general educational environment (Emam & Mohamed, 2011). Egypt's IE schema, like most developing countries, is gradually shifting from a rationale for why this discourse should be pursued, to how it can be efficaciously adopted (Emam, 2016; Toson et al., 2013). Arab countries are titanically struggling to provide education for a dramatically growing number of individuals having mild disabilities in an educational context that is deemed ‘less restrictive’ rather than ‘least restrictive’ (Alkhateeb et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dalam temuanya disebutkan beberapa faktor yang menjadi problem sekolah inklusi: (a) adanya orang tua siswa dan masyarakat yang tidak menerima siswa masuk di sekolah regular; (b) kualitas guru yang tidak dibekali dengan pengetahuan konsep pendidikan inklusi ; (c) hubungan yang tidak harmonis antara pengelola sekolah dengan guru pendamping. Kedua mengkaji tentang perbandingan konsep sekolah inklusi dengan negara lain (Emam, 2016). Sedangkan, kajian tentang pengelolaan sekolah inklusi pada sekolah yang dikelola yayasan Islam belum banyak dijumpai oleh peneliti.…”
Section: Pendahuluanunclassified
“…According to the OECD Education Working Paper (2022) that gives the social and economic rationale of inclusive education and overviews the outcomes in education for diverse groups of students, inclusive education "has become a core concept in education theory discourse over the last few decades" (p.7). In Oman, though inclusive education and the special education services are relatively new (Emam, 2017), the efforts of the Omani government to protect the rights of people with disabilities to education (Welfare and rehabilitation law, 2008) and provide them with the necessary facilities, materials and resources are enormous and widely acknowledged. In agreement with Oman Vision 2040 policy document, inclusive education is one of strategic directions and national priorities in the areas of education, scientific research and national talents that are aimed at creating a highquality educational system with communal partnerships that empowers human capabilities (Oman Vision 2040, n.d., n.p.).…”
Section: Introductionmentioning
confidence: 99%
“…The ideas on inclusive education have been sharpened and elaborated in academic and public discussions and publications by local researchers in Oman. Emam (2017), for example, examined how inclusive education is managed in Oman's schools, while specifically focusing on challenges and tensions between theory and practice, as well as strengths and difficulties. The researcher suggested basing inclusive education discourse on empirically validated perspectives to advance it and develop a framework for action.…”
Section: Introductionmentioning
confidence: 99%